Effect Of Adding Polymer (SAP) And Spraying Anti-Transpiration Kaolin And Yeast On Some Indicators Of Vegetative Growth And Some Chemical Traits Of Leaves Of Carica Papaya L (Journal of Pharmaceutical Negative Results, 2022)
During the growing season of 2021, an experiment was conducted on a papaya plant at the research station of the College of Agriculture and Marshlands, Dhi Qar University, to determine the impact of adding various levels of SAP agricultural polymer (0, 50, 100) g. m-2, anti-transpiration kaolin at levels (0, 1, 3) g.L-1, and baking yeast at two levels (0, 20) g.L-1. In terms of several chemical properties and characteristics of vegetative development, The results showed that the yeast spray (20 g.L-1), the anti-transpiration therapy (3 g.L-1), and the polymer addition treatment (100 g.m-2) were the most effective treatments. The complete random block design was utilized with three replicates. In comparison to the other treatments, they produced plants with the maximum height, leaf area, stem diameter, number of leaves, chlorophyll content, and leaf carbohydrate content.